2021
DOI: 10.1007/s00405-021-06868-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between IL-6 serum level and olfactory dysfunction severity in COVID-19 patients: a preliminary study

Abstract: Background Interleukin 6 (IL-6) is a proinflammatory cytokine that is secreted by cells infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and it is widely recognized as a negative prognostic factor. The purpose of this study was to analyze the correlations between the olfactory scores determined by psychophysical tests and the serum levels of IL-6 in patients affected by coronavirus disease 2019 (COVID-19) Methods Patients underwen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
3
22
1
Order By: Relevance
“…However, no clinical, epidemiological or laboratory risk factors have yet been identified [32,33]. In this study including 288 patients with COVID-19 OD, it is confirmed that no clinical or epidemiological factor predicts the evolution of OD at 2 months.…”
Section: Discussionsupporting
confidence: 66%
“…However, no clinical, epidemiological or laboratory risk factors have yet been identified [32,33]. In this study including 288 patients with COVID-19 OD, it is confirmed that no clinical or epidemiological factor predicts the evolution of OD at 2 months.…”
Section: Discussionsupporting
confidence: 66%
“…It has not yet been clarified what the frequency of persistent disturbances is in these groups of individuals, but if the prevalence recorded in cases of primary infection were confirmed, it would mean that this problem may not end with the immunization of the population. Second, the identification of the pathogenesis [54][55][56][57][58][59][60][61] and risk factors [2][3][4][5][6][7][8][9][10][11][12][62][63][64][65][66][67][68] for the development of persistent CD are in its infancy. For this reason, no effective therapies have yet been found for the prevention and treatment of COVID-19 related POD and PGD [69][70][71][72][73][74][75].…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, we would like to comment on the publication “Correlations between IL-6 serum level and olfactory dysfunction severity in COVID-19 patients: a preliminary study [ 1 ].” Vaira et al concluded that “In COVID-19 patients, psychophysical olfactory scores did not show significant correlations with the plasma levels of a well-recognized negative prognostic factor such as IL-6. This observation casts some shadows on the positive prognostic value of olfactory dysfunctions.…”
mentioning
confidence: 99%
“…This observation casts some shadows on the positive prognostic value of olfactory dysfunctions. [ 1 ].” We agree that it is interesting to try to find clinical correlation between olfactory symptom and a laboratory parameter for inflammation. Regarding IL-6, it is an inflammatory marker and might be associated with many confounding factors.…”
mentioning
confidence: 99%